2020
DOI: 10.1111/jcpe.13397
|View full text |Cite
|
Sign up to set email alerts
|

Immediate implant placement with or without connective tissue graft: A systematic review and meta‐analysis

Abstract: ObjectivesTo assess the effect of connective tissue graft (CTG) in terms of vertical mid‐facial soft tissue change when applied at the buccal aspect following single immediate implant placement (IIP).Materials and methodsTwo independent reviewers conducted an electronic literature search in PubMed, Web of Science, EMBASE and Cochrane databases as well as a manual search to identify eligible clinical studies up to January 2020. Randomized controlled trials (RCTs) and non‐randomized controlled studies (NRSs) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 113 publications
5
70
1
2
Order By: Relevance
“…These values are in line with those obtained in the present study. The results of this study agree with a recent meta-analysis study in which significant differences were not found between immediate implants with or without CTG with regard to marginal bone resorption ( p = 0.42) [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These values are in line with those obtained in the present study. The results of this study agree with a recent meta-analysis study in which significant differences were not found between immediate implants with or without CTG with regard to marginal bone resorption ( p = 0.42) [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several publications have investigated the tridimensional changes after immediate implants placed with SST or CTG, but no study has compared both techniques on immediate implants [ 18 , 19 , 20 ]. Therefore, this study aimed to observe the dimensional changes in peri-implant tissues after the placement of immediate postextraction implants and the performance of connective tissue graft and/or socket shield.…”
Section: Introductionmentioning
confidence: 99%
“…A radiographic, histologic, or clinical distinction should be made to identify the nature of the peri‐implant hard‐tissue structure, and its implications. After tooth extraction, the horizontal resorption is the most pronounced, compared with the vertical resorption 66,67 . Mitigating horizontal bone resorption in sites with thin buccal plate (≤2 mm) would provide the patients with many benefits; especially in the esthetic zone 66‐68 .…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 67 Mitigating horizontal bone resorption in sites with thin buccal plate (≤2 mm) would provide the patients with many benefits; especially in the esthetic zone. 66 , 67 , 68 These benefits include better and stable peri‐implant soft‐tissue esthetics, in addition to improved implant function, and hygiene. 54 , 69 , 70 Thin biotype and inadequate oral hygiene are risk factors for developing peri‐implantitis and subsequent reduction in the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, thick soft tissue can even mask and hide alveolar bone loss on the buccal side of implants [12,13,15]. Therefore, soft tissue augmentation is recommended in esthetical regions where a certain amount of buccal bone remodeling is expected, like immediate implant placement in situations with thin biotype or thin buccal bone plate [17,18].…”
Section: Esthetic Appearancementioning
confidence: 99%